MENGGAGAS EPISTEMOLOGI DALAM FILSAFAT ISLAM - Ahmad Maliki (STAI Sufyan Tsauri Majenang, 2021)
This research is libraray research, the purpose of this research is to find common geroun two epistemological feature of Platonic rasionalism and Aristotalian empiricism. It cannot be denied rasionalism and empiricism give colors for the development of philosophy, both Western Philosophy and Eastern Philosophy, espesily Islamic Philosophy. But it does not stop at the realm of philosophy, even developments in the field of knowledge are marked by the two epistemologies. When rasionalim reaches its peak and empiricism reaches its peak efforts to find the two schools, especially in the West, were not made until finally Imanuel Kant (1724-1804) appeared very sharply to criticize and straighten the exclusivity of the two schools.In contrast to the Islamic world, efforts to reconcile the two epistemologies in a peaceful manner were always attempted from the Classical to the Middle Ages. Mulla Sadra, a mystical philosopher, was able to bring together the two very beautifully, even transformed into a major sect in Islamic philosophy, namely Hikmah Muta'aliyah. To arrive at true knowledge reason alone is not sufficient, but requires action (worship, demonstration methods) that lead to the purity of the Soul to attain kasyf or disclosure. A typical Islamic epistemology that combines revelation and human reason. The clearer the combination of sharia, tarikat, ma'rifat and essence.